1999
DOI: 10.1002/1529-0131(199907)42:7<1361::aid-anr9>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of exercise therapy in patients with osteoarthritis of the hip or knee: A systematic review of randomized clinical trials

Abstract: Objective. To review the effectiveness of exercise therapy in patients with osteoarthritis (OA) of the hip or knee.Methods. A computerized literature search of Medline, Embase, and Cinahl was carried out. Randomized clinical trials on exercise therapy for OA of the hip or knee were selected if treatment had been randomly allocated and if pain, self-reported disability, observed disability, or patient's global assessment of effect had been used as outcome measures. The validity of trials was systematically asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
379
4
30

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 476 publications
(427 citation statements)
references
References 41 publications
(46 reference statements)
10
379
4
30
Order By: Relevance
“…4,5 Although ET has demonstrated beneficial effects for hip OA in recommended core outcomes 6 of pain 7,8 and patient perceived improvement (patient global assessment-(PGA) 9,10 in the short and medium term, results for changes in physical function are conflicting. A number of randomised controlled trials (RCTs), some of which have included participants with hip or knee OA, found functional benefits with exercise 9,11,12 , but a meta-analysis, based on data from participants with hip OA only, found no effect on physical function 7 .…”
Section: Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Although ET has demonstrated beneficial effects for hip OA in recommended core outcomes 6 of pain 7,8 and patient perceived improvement (patient global assessment-(PGA) 9,10 in the short and medium term, results for changes in physical function are conflicting. A number of randomised controlled trials (RCTs), some of which have included participants with hip or knee OA, found functional benefits with exercise 9,11,12 , but a meta-analysis, based on data from participants with hip OA only, found no effect on physical function 7 .…”
Section: Authorsmentioning
confidence: 99%
“…However, some of these studies included people with hip or knee OA 9, 10, 43 , so the evidence regarding the optimal exercise approach for hip OA alone has yet to be identified. A moderate treatment effect on pain for hip OA has been ascertained in two meta-analyses 7,8 with no significant effect on function, based on five RCTs 7 . The original RCTs which demonstrated a benefit of ET included data from trials which included participants with hip or knee OA 9,11,43 whereas the meta-analysis extracted hip OA data only.…”
Section: Secondary Aimmentioning
confidence: 99%
“…Results have demonstrated that psychological factors (9 -13), demographic and clinical factors (9,11,14), biomechanical factors (10,15,16), and treatment modalities (10,17) are associated with disability. It is not known, however, whether these factors also predict future disabil-ity.…”
Section: Introductionmentioning
confidence: 99%
“…Results of short-term studies have suggested the greater benefit of combined approaches (e.g., acupuncture/diet/exercise versus pain therapy alone [49]). Moreover, the effect sizes for strengthening interventions appear to be enlarged by incorporating pain management, attention to psychosocial factors, self-management, or aerobic exercise into the intervention (50,51).…”
mentioning
confidence: 99%